Research on Construction and Interoperability of Complex Distributed Simulation System - Li, Ning; Wang, Zhou; Liu, Wei-Hua; Peng, Xiao-Yuan; Gong, Guang-Hong (Systems Modeling and Simulation: Theory and Applications, 2005)
This paper presents an assumed interoperability framework of Complex Distributed Simulation System (CDSS). On the basis of it, interoperability conceptual model of C4I simulation system, distributed weapon platform Modeling and Simulation (M&S) system and Synthetic Natural Environment (SNE) is proposed. Key technologies such as C4I modeling and simulation, SNE modeling to construct CDSS and achieve interoperability are discussed. The interoperability Data Interchange Format (DIF) based on HLA OMT, called CDSS FOM, is given and introduced, which is applied in the Attack-Defense Simulation System.